2005
DOI: 10.7824/rbh.v4i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da chuva sobre a eficácia de diferentes formulações de glyphosate no controle de Bidens pilosa

Abstract: Foi objetivo deste trabalho avaliar os efeitos de doses crescentes de diferentes sais de glyphosate -amônio (Roundup WG), isopropilamina (Roundup Transorb) e potássico (Zapp Qi) -sobre as plantas de Bidens pilosa em condições controladas, quando submetidas à chuva de 20 mm durante 30 minutos, nos intervalos de 1, 2, 4, 6, 12 e 24 horas após aplicação desses produtos. A eficiência de controle de B. pilosa pelos sais de glyphosate foi afetada quando ocorreu chuva após aplicação. A redução no controle foi maior à… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…RW GSA treatment, which constitutes the commercial product Roundup WG ® , which formulation is in ammonium salt, was what caused most poisoning plants, not significantly differing from the CRUCIP treatment which is Crucial ® and its formulation is based on potassium salt and isopropylamine salt (Table 2). In this case, greater control of benghal dayflower species was made with application of glyphosate formulation in ammonium salt, other authors also obtained similar results in similar conditions compared to other formulations in benghal dayflower weed (Oliveira et al, 2009), beggartick (Bidens pilosa) (Werlang et al, 2005) and southern cutgrass (Leersia hexandra e Luziola peruviana) (Scherner et al, 2014).…”
Section: Resultssupporting
confidence: 58%
“…RW GSA treatment, which constitutes the commercial product Roundup WG ® , which formulation is in ammonium salt, was what caused most poisoning plants, not significantly differing from the CRUCIP treatment which is Crucial ® and its formulation is based on potassium salt and isopropylamine salt (Table 2). In this case, greater control of benghal dayflower species was made with application of glyphosate formulation in ammonium salt, other authors also obtained similar results in similar conditions compared to other formulations in benghal dayflower weed (Oliveira et al, 2009), beggartick (Bidens pilosa) (Werlang et al, 2005) and southern cutgrass (Leersia hexandra e Luziola peruviana) (Scherner et al, 2014).…”
Section: Resultssupporting
confidence: 58%
“…When comparing the results in each environment, it was observed that the necessary dose to obtain 90% of control in the field for black picker was 10 and 19 times greater than the experiment in greenhouse and BOD, and for horseweed, it was 8 and 22 times greater, respectively. The differences across the control levels observed in the field may be a result of the environmental factors, such as soil humidity, radiation, temperature and relative air humidity, which may affect the characteristics of the plant, such as inducing the development of a thicker cuticle, trichomes and deeper root system, and the efficiency of the herbicide, since in BOD and in the greenhouse there is a greater control over these factors (Werlang et al, 2005). These results show the importance of the environmental conditions to the quality of the application and the control results obtained with saflufenacil in the studied species.…”
Section: (A) (D) (B) (E) (C) (F)mentioning
confidence: 99%
“…Its formulation contains the isopropylamine which also is also present in Roundup Original formulation (Rodrigues and Almeida, 2005). Different formulations can change the absorption and translocation of the herbicide, influencing the control efficiency (Silva et al, 2006) and its behavior in the environment (Werlang et al, 2005;Santos et al, 2007).…”
Section: Introductionmentioning
confidence: 99%